Antitumor effects of Dadas Cress (Lepidium sativum var. sativum) on Ehrlich Ascites tumor cells: an in vitro and in vivo study - Ünalmış Aykar, Demet; Ülger, Harun; Doganyiğit, Züleyha; Şeker Karatoprak, Gökçe; Pandır, Dilek; Uçar, Sümeyye; Kaymak, Emin; Okan Oflamaz, Aslı; Yılmaz, Seher (Springer Science and Business Media LLC, 2025)
Garden cress (Lepidium sativum L.) is widely used in nutrition and traditional medicine for its bioactive properties.
Studies show its seeds and leaves have anticancer, antimicrobial, and antidiabetic effects. This study investigated the antitumor
potential of an extract from the leaves of Dadaş cress (Lepidium sativum var. sativum), a Turkish variety, against
Ehrlich Ascites Tumor (EAT) cells. In the in vitro study, Dadaş cress extract (DCE) was tested at 25, 50, and 100 μg/mL
concentrations to evaluate its antitumor activity. Caspase-3/7 activity was measured by fluorometric assay, mitochondrial
membrane depolarization by JC-1 dye, and cell cycle by flow cytometry. The 50 μg/mL group had the highest apoptosis
rate at 48 h; 100 μg/mL caused the most mitochondrial depolarization at 24 h. After 72 h, the 5-FU group had the highest
G0/G1 phase cells, while the 25 μg/mL DCE group had the highest S phase cells. In vivo, groups were control, EAT
control, EAT + 5-FU, EAT + DCE (75–150 mg/kg), and DCE only (75–150 mg/kg). Liver and kidney tissues were examined
immunohistochemically, biochemically, and genotoxically. DCE significantly lowered TNF-α expression, oxidative
stress, and DNA damage in EAT mice. In the 150 mg/kg DCE group, renal tail DNA% dropped from 92.5 to 34.8%, liver
tail DNA% from 105.3 to 65.8%. TAS increased, TOS decreased vs. EAT control (p < 0.05). These results suggest DCE
protects against EAT-induced damage dose-dependently and has no genotoxicity. The findings suggest that DCE may have
antitumor potential.
Keywords Antitumor effect · Apoptosis · EAT · Garden cress